THE ECONOMICS OF CYBER SECURITY IN THE ENERGY INDUSTRY AND ITS ASSESSMENT METHODS - Koraboev , Eldor Alijonovich (Innovative Development in Educational Activities, 2023)
In this paper, relevant methods, mechanisms and models for assessing the cyber security economy of energy industry enterprises are presented. Moreover, the author’s approach is also presented.